E-Learning Module Music In PGSD FIP UNM - Sayidiman Sayidiman; Hikmawati Usman; Nasaruddin Nasaruddin; Muh. Faisal; Lutfi Lutfi (Prodi PGSD FIP UNM, 2020)
This research was conducted to design and test on a small scale the results of the design of the art learning module Music at the PGSD FIP UNM. In particular, this study aims to describe the description of the design of music e-learning modules in the UNM FIP PGSD Study Program. The research method used research development (R & D), the test subjects were the PGSD FIP UNM students who had programmed the Music Arts course. Sampling is done by using a simple random sampling technique with a number of sample members of 30 people, the data collection techniques using a closed questionnaire, analysis of data using the data analysis descriptive and inferential statistics. The results Showed that there was an Increase in participation and student learning outcomes classically after learning to use e modules, the weakness of e modules was that they were not Able to encourage students who had the ability more towards Reviews their maximum potential in terms of learning the art of music.